3D-oblikovanje in vizualizacija s programom Google SketchUp - Dolenc, Kosta (Revija za elementarno izobraževanje, 2011)
3d Design and Visualization With the Computer Program Google Sketchup. This article presents reasons for using a 3D designing program and Google Sketch Up visualization in Engineering and technology classes in primary school. Emphasis is given to the analysis of the current condition of this topic and on incorporating the program into lesson plans. With strategies that utilize such programs, we can strengthen abilities that are connected with technological activities, develop spatial intelligence and assimilate, acquire and reinforce two key European competences: mathematical competence and basic competences in science, technology and digital literacy.
Keywords: engineering and technology; Google SketchUp; spatial intelligence; competence; ability